ANALISIS PERENCANAAN DAN PENGANGGARAN RESPONSIF ANAK (PPRA) SEBAGAI PERWUJUDAN KOMITMEN PEMERINTAH KOTA SEMARANG DALAM PENCAPAIAN KOTA LAYAK ANAK (KLA) - Evi Widowati; Fafurida Fafurida; Lita Latiana (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
The fulfillment of children's rights and special protection for the children as regulated in Law Number 23 Year 2014 as a revision of Law Number 32 Year 2004 regarding Regional Government, is a mandatory government-mandated non-basic affair. So the responsibility to meet the needs of children's rights and provide special protection for children is not only a burden to the central government, but also the responsibility of local governments. One way to find out the commitment of local governments in making efforts to fulfill the rights of the children and special protection for the children is to look from the planning and budgeting for the implementation of programs and activities that support the fulfillment of the children's rights and special protection for the children in the region. This research uses descriptive quantitative research design. Technique of collecting data is through secondary data at OPD in charge related to planning and budgeting that is Bappeda and DPPKA. From the results of this study shows that the picture of child responsive budgeting in the last three years at the Regional Government of Semarang City in 2014 reached 5.951%, in 2015 rose to 8.775% and in 2016 increased again to 9.521%. So it can be said that the commitment of Semarang City Government is quite good and consistent to fulfill the rights of the children even though the percentage is still relatively small. While the description of budget realization for the last three years reveals that is the highest achievement of the cluster IV and the lowest in cluster I. On the other side still found 4 Indicators that have not been backed-up adequate on the budget of 13 key OPD namely: 1 indicator on cluster 1 and 3 indicator on cluster 5. Suggestions include: enhancing the role of Bappeda as KLA task force coordinator in coordinating across sectors to increase commitment to the fulfillment of the children's rights to all OPD especially related to planning and budgeting aspects, revitalizing the role of KLA task force, advocating, socializing and technical guidance of implementation of PPRA in all OPD in Semarang City.